ANALISIS PENGARUH KUALITAS JASA TERHADAP KEPUASAN DIKLAT DI BLPT YOGYAKARTA DAN DAMPAKNYA PADA LOYALITAS KONSUMEN - Siti Nurhayati (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2016)
The research aims to analyzing the influence of service quality at customer satisfactiondiklat in BLPT Yogyakarta and its impact at consumer loyalty. The population is consumer (studentof SMK Industrial and Technological group country goodness and private sector, technique studenteither from college of private sector and country, governmental institution/private sector,corporate, and public society). Population in this research have location in Jl. Kyai Mojo No. 70Yogyakarta. Method intake sampels in this research use Probability Sampling, the technics usingSimple Random Sampling. Amount of used sampel counted 165 respondent, but after conducted byspreading of kuisioner only 150 kuisioner able to be processed. In this research, hypothesis testconducted by using Linear Multipel Regression analysis and Simple Linear Regression, usingprogram SPSS 12.00 for windows, this is needed to know influence of independent variable todependent variable. Examination of yielded parameter values will be conducted using t-test, F-testand determinasi coefficient (R2)The result of this research confirm that the service quality of reliability (X1), assurance(X3) and of tangibles (X5) have an signifikan effect at consumer satisfaction of diklat in BLPT,while service quality of responsiveness (X2) and emphaty (X4) do not have an signifikan effect atconsumer satisfaction of diklat in BLPT. Consumer satisfaction have an signifikan effect atconsumer loyalty. Consumer satisfaction also represent intervening variable between servicequality and consumer loyalty.Keyword : service quality factors, consumer satisfaction, loyalty consumer